Ink-jet printing of transparent and stretchable electrodes for dielectric elastomer actuator - Shrestha, Milan (2018)
Dielectric elastomer actuators have recently been used to drive loudspeakers and acoustic absorbers. So far, these acoustic devices are opaque due to use of metallic or carbongrease compliant electrodes. A transparent device of acoustic-absorber is desirable for large-areal installation to glass window or roof. There were reports of transparent compliant electrode based on ionic hydrogel, which however does not last long when water evaporates. This paper investigates the use of transparent conductive polymer and its printing to make a transparent acoustic absorber. We formulated the aqueous ink with improved ink’s wettability to the elastomeric substrate. In addition, we optimized the droplet spacing to form a continuous electrode coating. The ink-jet printing enables the hassle-free patterning of transparent compliant electrodes to make a micro-perforated dielectric elastomer actuator. Testing shows that this transparent membrane DEA can produce a maximum voltage-induced radial expansion of 20%; whereas, a transparent perforated-membrane DEA can size down the holes by 15%, for tuning the acoustic resonant frequency.